1962
DOI: 10.1017/s0003356100034280
|View full text |Cite
|
Sign up to set email alerts
|

Characters of economic importance in Welsh Mountain sheep

Abstract: 1. The influence of seasonal, maternal and genetic variation on body weight and fleece characters of Welsh Mountain sheep is reported.2. Fertility and rearing ability of ewes improved from first to third lamb crop.3. Male lambs were on average 0·4 lb. heavier at birth than females. Birth weight increased with number of pregnancies of the dam.4. Early growth of the lamb between birth and marking (24 days old) used partly as a measure of milk production of the ewe, was greater in males than in females. Lambs bor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1964
1964
1997
1997

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 6 publications
1
14
0
Order By: Relevance
“…Turner (1956) reviewed the literature for staple length and found estimates ranging between 0.6 and 0.7. This is in good agreement with later findings of Young et al (1960a), Battie (1961) and Dalton (1962) while Katada & Takeda (1959) and Knothe (1964) found lower estimates (0.31 to 0.61). Thus the repeatability of 0.64 estimated on these data is in close agreement with earlier estimates.…”
Section: Repentobility For Wool Qirolity Troits Arid Wool Weight Ofsupporting
confidence: 93%
See 1 more Smart Citation
“…Turner (1956) reviewed the literature for staple length and found estimates ranging between 0.6 and 0.7. This is in good agreement with later findings of Young et al (1960a), Battie (1961) and Dalton (1962) while Katada & Takeda (1959) and Knothe (1964) found lower estimates (0.31 to 0.61). Thus the repeatability of 0.64 estimated on these data is in close agreement with earlier estimates.…”
Section: Repentobility For Wool Qirolity Troits Arid Wool Weight Ofsupporting
confidence: 93%
“…Repeatability for British breeds ranged from 0.4 t o 0.6. Additional estimates of repeatability of greasy fleece weight are in good agreement with the former and that given in Table 5 (Blackwell & Henderson, 1955;Katada & Takeda, 1959;Young el al., 19600;Battie, 1961;Dalton, 1962;Knothe, 1964;Nel, 1964 andYalqin &Bichard, 1964).…”
Section: Repentobility For Wool Qirolity Troits Arid Wool Weight Ofmentioning
confidence: 99%
“…These effects are likely to be both pre-natal (Dalton 1962;Hight & Jury 1970) and post-nataL Hunter (1956) showed that milk production in ewes increased with age. The advantage of TS over IT is likely to reflect extra milk received.…”
Section: Discussion Environmental Variation In Hogget Traitsmentioning
confidence: 99%
“…Estimates for British breeds ranged from 0.4 to 0.6. Additional estimates given by Blackwell & Henderson (1955), Dalton (1962), Yalcin & Bichard (1964) and Nel et al (1972) vary between 0.42 and 0.61.…”
Section: Repea F a Bilit Iesmentioning
confidence: 88%